Determining the Association between Aeration in the Rhizosphere and P-Acquisition Strategies: Constructing Efficient Vegetable Root Morphology - Wang, Rui; Shi, Weiming; Li, Yilin (Current Advances in Geography, Environment and Earth Sciences Vol. 6, 2022)
A low P absorption and utilization rate is one of the important obstacles restricting vegetable production. The characteristics of the vegetable shallow root system and immobility of P in the soil aggravated the contradiction between P demand and supply in the vegetable rhizosphere. Therefore, a large amount of phosphate fertilizer applied in vegetable fields to maintain high P content in the root zone, led to the deterioration of the vegetable rhizosphere environment, especially the soil O2 environment, which had a feedback effect on the root morphological structure and vegetable yield. Nevertheless, the interaction between root morphology and rhizosphere oxygen environment responses to vegetable P utilization are rarely reported. In order to explore the impact on root morphology, P adsorption, and its mechanism, we conducted an experiment using varying concentrations of O2 generator, 10%, 30%, 50%, and 80% urea hydrogen peroxide (as pure nitrogen) instead of urea as a top dressing in the rhizosphere. We discovered that the rhizosphere had O2- and P-deficient zones, and that oxygenation might reduce the roots' rhizosphere O2 and P consumption. The features of the root morphology and enhanced availability of P in the rhizosphere jointly contributed to high P absorption and use, and in the 30% urea hydrogen peroxide treatment compared to CK, the P use efficiency was improved by 9.3% and the shoot P accumulation by 10.9%. Additionally, this procedure increased quality and yield, as well as the amount of vitamin C and soluble sugar. However, vegetable development showed O2 damage at a higher O2 level (260.8 \(μ\)mol L-1), leading in a lower yield and lower quality. Our research offered fresh perspectives on designing effective root morphology by controlling the rhizosphere's O2 environment to boost P usage efficiency in vegetable fields and raise vegetable output and quality.